MicroRNA‐132 is overexpressed in glia in temporal lobe epilepsy and reduces the expression of pro‐epileptogenic factors in human cultured astrocytes. Issue 1 (13th August 2019) - Korotkov, Anatoly; Broekaart, Diede W. M.; Banchaewa, Leyla; Pustjens, Ben; van Scheppingen, Jackelien; Anink, Jasper J.; Baayen, Johannes C.; Idema, Sander; Gorter, Jan A.; van Vliet, Erwin A.; Aronica, Eleonora
Abstract: Temporal lobe epilepsy (TLE) is a chronic neurological disease in humans, which is refractory to pharmacological treatment in about 30% of the patients. Reactive glial cells are thought to play a major role during the development of epilepsy (epileptogenesis) via regulation of brain inflammation and remodeling of the extracellular matrix (ECM). These processes can be regulated by microRNAs (miRs), a class of small non‐coding RNAs, which can control entire gene networks at a post‐transcriptional level. The expression of miRs is known to change dynamically during epileptogenesis. miR‐132 is one of the most commonly upregulated miRs in animal TLE models with important roles shown in neurons. However, the possible role of miR‐132 in glia remains largely unknown. The aim of this study was to characterize the cell‐type specific expression of miR‐132 in the hippocampus of patients with TLE and during epileptogenesis in a rat TLE model. Furthermore, the potential role of miR‐132 was investigated by transfection of human primary cultured astrocytes that were stimulated with the cytokines IL‐1β or TGF‐β1. We showed an increased expression of miR‐132 in the human and rat epileptogenic hippocampus, particularly in glial cells. Transfection of miR‐132 in human primary astrocytes reduced the expression of pro‐epileptogenic COX‐2, IL‐1β, TGF‐β2, CCL2, and MMP3. This suggests that miR‐132, particularly in astrocytes, represents a potential therapeutic target that warrants further in vivo investigation. Main Points: miR‐132 expression is increased in the epileptogenic human and rat hippocampus. miR‐132 is expressed by reactive glia. miR‐132 attenuates expression of pro-epileptogenic factors in cultured human astrocytes.